PENGARUH MOTIVASI DAN EFIKASI DIRI TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI DI SMK KABUPATEN PEMALANG - Toto Sudarmo, 12.5202.0173; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study was to investigate the efficacy of motivation and the performance of teachers. The specific objectives of this study is to examine and analyze whether work motivation and self-efficacy moderated by organizational culture. The research data is primary data collected directly from the respondents to the questionnaire. The method of data analysis using Moderation Regression Analisys (MRA)-type quasi moderator. The results showed that motivation, self-efficacy and organizational culture significantly influence the performance of teachers. In addition to the organizational culture does not moderate the effect of teacher performance and motivation with organizational culture did not moderate the effect of self-efficacy with the teacher's performance. Keywords: motivation, self-efficacy organizational culture, teacher performance.